2017
DOI: 10.1590/1413-82712017220101
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades Sociais e Bem-Estar Subjetivo de Crianças Dotadas e Talentosas

Abstract: ResumoO desenvolvimento socioemocional de crianças dotadas e talentosas ainda é objeto de controvérsias na literatura especializada. Este estudo visou avaliar a relação entre habilidades sociais e bem-estar subjetivo de crianças dotadas e talentosas e identificar o poder preditivo da primeira variável sobre a segunda. Participaram 269 crianças, de ambos os sexos, identificadas como dotadas e talentosas, de oito a 12 anos, que responderam a instrumentos padronizados de medida das habilidades sociais e de bem-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
2
0
7
Order By: Relevance
“…Understood as the cognitive dimension of well-being, satisfaction with life can evidence the way students face adversities in their daily lives in subjective, interpersonal, and affective terms (Long & Huebner, 2014). In this sense, the results of the present study are in line with other studies that indicated that exposure to family violence negatively influences life satisfaction (Silva & Dell'Aglio, 2016), while social skills and perceptions of social support increase their levels (França-Freitas et al, 2017;Sarriera et al, 2015), suggesting the amortizing and protective effect of the mentioned variables. In addition, according to the literature (Berger et al, 2011;Long & Huebner, 2014), the results showed that students with better school results had higher levels of satisfaction with life.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Understood as the cognitive dimension of well-being, satisfaction with life can evidence the way students face adversities in their daily lives in subjective, interpersonal, and affective terms (Long & Huebner, 2014). In this sense, the results of the present study are in line with other studies that indicated that exposure to family violence negatively influences life satisfaction (Silva & Dell'Aglio, 2016), while social skills and perceptions of social support increase their levels (França-Freitas et al, 2017;Sarriera et al, 2015), suggesting the amortizing and protective effect of the mentioned variables. In addition, according to the literature (Berger et al, 2011;Long & Huebner, 2014), the results showed that students with better school results had higher levels of satisfaction with life.…”
Section: Discussionsupporting
confidence: 89%
“…Social skills are defined as behaviors valued in a particular culture and historical moment and contribute to positive interpersonal relationships, as well as for the maintenance and/or enhancement of Human Rights (Del Prette & Del Prette, 2010). Studies have shown associations between higher levels of social skills of students both with life satisfaction and good school results (Caemmerer & Keith, 2015;França-Freitas, Del Prette, & Del Prette, 2017;Fernandes et al, 2018;Ronen, Hamama, Rosenbaum, & Mishely-Yarlap, 2016).…”
mentioning
confidence: 99%
“…Outro instrumento que se destacou, e que também avalia aspectos positivos, foi a Escala Multidimensional de Satisfação de Vida para Crianças (EMSVC) desenvolvida para o contexto brasileiro por Giacomoni e Hutz (2008), foi citada em três estudos que correlacionaram o bem-estar subjetivo a outros construtos, como otimismo (Bandeira, Natividade, & Giacomoni, 2015) habilidades sociais e dotação (Freitas, Del Prette, & Del Prette, 2017a;Freitas, Del Prette, & Del Prette, 2017b). Nos três casos os resultados da EMSVC foram correlacionados aos da Escala de Afetos positivos e Negativos para crianças, desenvolvida pelos mesmos autores brasileiros (Giacomoni & Hutz, 2006).…”
Section: Resultsunclassified
“…O desenvolvimento socioafetivo e a educação afetiva tem sido pauta de pesquisas, políticas públicas e educacionais. Há uma emergência de abordagens que relacionam aspectos desse desenvolvimento com bem-estar subjetivo, qualidade de vida, sucesso escolar e saúde mental (Cavilla, 2016;França-Freitas, Del Prette, & Del Prette, 2014). Estudiosos evidenciam a importância de uma formação integral do indivíduo, ressaltam a necessidade do jovem contemporâneo estar preparado para enfrentar problemas de diferentes magnitudes e ponderam que as habilidades necessárias à sua solução dificilmente serão contempladas plenamente em propostas curriculares que enfatizam apenas uma faceta do processo de aprendizagem (Abed, 2014;Santos & Primi, 2014).…”
unclassified
“…Verifica-se que a possibilidade da ocorrência do desajustamento social não é inerente ao indivíduo talentoso, mas fruto da interação entre suas características pessoais e o ambiente em que está inserido. Pesquisadores da área evidenciam que indivíduos com altas habilidades e com tais características em contextos ambientais apropriados apresentam ajustamento e maturidade socioemocional acima da média, comparados aos seus pares (Fleith, 2007;França-Freitas et al, 2014;Neihart, Reis, Robinson, & Moon, 2002;Neihart, Pfeiffer & Cross, 2016;Prado & Fleith, 2017;Virgolim, 2007). Essa constatação ratifica a necessidade de programas de apoio ou aconselhamento a esses jovens bem como de esclarecimentos aos pais e professores.…”
unclassified